2017
DOI: 10.1108/ijqrm-03-2015-0045
|View full text |Cite
|
Sign up to set email alerts
|

5S – a quality improvement tool for sustainable performance: literature review and directions

Abstract: Purpose The purpose of this paper is to present the comprehensive literature review on 5S and suggest possible gaps from the point of view of researchers and practitioners. The manuscript presents the overview of 5S implementation and highlights the achievements realized from deployment of 5S initiatives for sustainable performance of organizations. Design/methodology/approach The paper critically examines the literature on 5S, analyzes and reviews it systematically. The study highlights the critical barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 75 publications
1
69
0
3
Order By: Relevance
“…[25,34] Several researches highlighted the significant contribution of implementing the 5S as a lean tool in their hospitals. For example, Randhawa and Ahuja (2017) clarified in their study that 5S initiated improvement in production, quality, safety, and effective utilization of workspace. [35] Also, Kanamori et al (2015) concluded that the intervention of the 5S was perceived to have improved quality of healthcare services and staff motivation in a facility with poor-resources and a disorderly work environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25,34] Several researches highlighted the significant contribution of implementing the 5S as a lean tool in their hospitals. For example, Randhawa and Ahuja (2017) clarified in their study that 5S initiated improvement in production, quality, safety, and effective utilization of workspace. [35] Also, Kanamori et al (2015) concluded that the intervention of the 5S was perceived to have improved quality of healthcare services and staff motivation in a facility with poor-resources and a disorderly work environment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Randhawa and Ahuja (2017) clarified in their study that 5S initiated improvement in production, quality, safety, and effective utilization of workspace. [35] Also, Kanamori et al (2015) concluded that the intervention of the 5S was perceived to have improved quality of healthcare services and staff motivation in a facility with poor-resources and a disorderly work environment. [36] On the contrary, Boswihi (2017) stated that the head nurses were not able to use the tool of 5S due to the design of the ward and the poorly disorganized working environment as their wards are crowded with equipment with no storage area.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved systematically by cleaning and standardizing the whole organizational workplace. The processes through which 5s goes through are sort, set in order, shine, standardize and sustain (Randhawa and Ahuja 2017). Kaizen also deals with continuous improvement process where everyone is encouraged to come up with small improvement suggestions on a regular basis, process oriented, not straight forward and difficult to sustain in the long run (Ma et al 2017).…”
Section: Lean Toolsmentioning
confidence: 99%
“…S3 Sweeping and Shining (Cleanliness), The third "S" directs the cleaning activities in the organization, include removal of dirt, grime, and dust from the workplace, and always keeping everything swept and clean (Chang, and Chen, 2014). On the other hand, daily cleanliness has to be done to have a normal work area, which more suitable and harmless workplace is ensured when the third S is implemented (Randhawa, and Ahuja, 2017), which a clean and organized work area itself acts as a motivation factor for the operators and workers that like work in a clean and good environment which boosts up their confidence (Dudek-Burlikowska, 2006). Teamwork members should apply the third "S" as an action to have to maintain cleanliness without being told to do so.…”
mentioning
confidence: 99%
“…Many factories do the 5S activities for months. But it converts very difficulty in sustaining the activities performed for a longer period (Randhawa, and Ahuja, 2017). Standards have to be maintained year after year in an effective manner (Dudek-Burlikowska, 2006).…”
mentioning
confidence: 99%